Strong Genetic Structure Observed in Primulina danxiaensis, a Small Herb Endemic to Mount Danxia With Extremely Small Populations - Chen, Sufang; Guo, Wei; Chen, Zaixiong; Liao, Wenbo; Fan, Qiang (Frontiers in Genetics, 2021)
Danxia landform is sporadically occurred in southern China, which has brought up abundant endemic species with extreme small populations. The speciation and conservation of these species has called widely scientific and public attentions. Primulina danxiaensis is a tiny perennial grass species recorded only in Danxiashan (named and famous for Danxia landform). The species occurs on wet and exposed rock surface in small population, and currently only 12 populations were found during years’ field investigations. In this study, restriction site-associated DNA sequencing (RAD-seq) was performed across the 94 individuals from 12 populations of P. danxiaensis. The results showed that the species possessed extreme low genetic diversity possibly due to founder effects detected in most populations. The 12 populations of P. danxiaensis could be further assigned into four clades in the phylogenetic tree corresponding to their geographic locations. This was also in accordance with Admixture analysis, in which all the 94 individuals could be classified into four gene pools. AMOVA analysis showed that 31.46% of genetic variation was observed among the four groups. Significant correlation was observed between genetic and geographic distances (r=0.572, P<0.001), indicating that P. danxiaensis individuals can be effectively isolated at a small spatial scale, leading to genetic differentiation among groups. Our study demonstrated that for plant species with extreme small populations, such as P. danxiaensis with low genetic diversity and strong population structure, measures should be taken to conserve all the populations.